1996
DOI: 10.1111/j.1532-950x.1996.tb01422.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Two Surgical Scrub Preparations in Cattle

Abstract: One hundred seventeen cattle that had undergone surgery were assigned randomly to two preoperative skin preparation protocols. Group 1 (60 animals) skin preparation was with povidoneiodine soap and isopropyl alcohol, whereas group 2 (57 animals) had skin preparation with chlorhexidine gluconate and isopropyl alcohol. Quantitative microbial culture plates were used to estimate the number of colony forming units (CFUs) before skin preparation (prescrub), after skin preparation (postscrub), after surgery (postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 24 publications
0
54
1
3
Order By: Relevance
“…In our study, there was no contamination from the periodic rinsing with 70% alcohol, and we concluded that a cleansing scrub of >5 min would have increased the bacterial reduction to a level comparable to the CG. In cattle, Desrochers et al (1996) reported similar results; CG resulted in a greater reduction in bacteria than PI after the cleansing scrub. The importance of bacterial reduction after the cleansing scrub is questionable, providing that sterile scrub is performed; however, in a clinical situation, where a sterile scrub is not performed, CG could be expected to perform better than PI.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In our study, there was no contamination from the periodic rinsing with 70% alcohol, and we concluded that a cleansing scrub of >5 min would have increased the bacterial reduction to a level comparable to the CG. In cattle, Desrochers et al (1996) reported similar results; CG resulted in a greater reduction in bacteria than PI after the cleansing scrub. The importance of bacterial reduction after the cleansing scrub is questionable, providing that sterile scrub is performed; however, in a clinical situation, where a sterile scrub is not performed, CG could be expected to perform better than PI.…”
Section: Discussionmentioning
confidence: 57%
“…In our study, there was no contamination from the periodic rinsing with 70% alcohol, and we concluded that a cleansing scrub of >5 min would have increased the bacterial reduction to a level comparable to the CG. In cattle, Desrochers et al . (1996) reported similar results; CG resulted in a greater reduction in bacteria than PI after the cleansing scrub.…”
Section: Discussionmentioning
confidence: 99%
“…A higher incidence of incisional complications following cleancontaminated emergency surgical procedures has been reported in Equidae compared to other species, with rates of 5% (Vasseur et al 1985(Vasseur et al , 1988 and 15% (Desrochers et al 1996) reported for small animals and cattle, respectively, compared to at least 24% in horses (Wilson et al 1995;Honnas and Cohen 1997;Ingle-Fehr et al 1997). Incisional complications, ranging from oedema and drainage to more serious complications, including infection and acute dehiscence, occur relatively commonly following exploratory celiotomy (Kobluk et al 1989;Wilson et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Tooth extraction is considered a contaminated procedure, which carries a risk of infection up to 27% in cattle. 28 Affected sites eventually healed without apparent deformation of the mandible or the maxilla at follow-up. Surgery involving the maxillary teeth seemed prone to perioperative complications, with postoperative SSI affecting all sites with maxillary sinus flaps.…”
Section: Discussionmentioning
confidence: 95%
“…Surgical site infection was the most frequent postoperative complication in this study and appeared to be more severe when retrograde repulsion was performed or when the dental plug was lost prematurely (<3 weeks postoperatively). Tooth extraction is considered a contaminated procedure, which carries a risk of infection up to 27% in cattle . Affected sites eventually healed without apparent deformation of the mandible or the maxilla at follow‐up.…”
Section: Discussionmentioning
confidence: 99%